Selective culinary uses of plant foods by Northern and Eastern European hunter-gatherer-fishers - Lara González Carretero; Alexandre Lucquin; Harry K. Robson; T. Rowan McLaughlin; Ekaterina Dolbunova; Jasmine Lundy; Giulia Moretti; Blandine Courel; Manon Bondetti; Marian Berihuete-Azorín; Daniel Groß; Jacek Kabaciński; et al. (PLoS ONE, 2026)
Carbonised food deposits preserved in pottery vessels, often termed ‘foodcrusts,’ are frequently encountered on hunter-gatherer-fisher (HGF) pottery throughout Northern and Eastern Europe. While lipid residue analysis is frequently employed to determine their composition, this technique favours the identification of animal products. In this study, we present a combined analytical approach, including high resolution microscopic analysis (Digital Microscopy and Scanning Electron Microscopy) together with molecular and isotopic analysis of lipids (GC-MS and GC-C-IRMS) and bulk isotope analysis (EA-IRMS) to further understand the composition of foodcrusts. Eighty-five pottery vessels with foodcrusts were analysed from 13 archaeological sites dating from the 6th to the 3rd millennium BC, of which 58 have allowed for identification of plant tissues, such as wild grasses and legumes, fruits, and the roots, tubers, leaves and stems of herbaceous plants. The results demonstrate that the choice of plant foods was remarkably selective, with hunter-gatherers favouring certain plant species and even their parts over others and combining these with specific animal ingredients. The results also reveal that our knowledge of plant processing in pottery is likely to be grossly under-represented by relying on lipid residue analysis alone.